Study on recrystallization process of nitroguanidine by directly adding cold water to control temperature - Zhang Jianjuan (Open Chemistry)
Nitroguanidine (NGu), as a kind of high-energy material, is widely used as explosive propellant and energy component of explosives and smokeless powder. However, NGu crystals prepared by crystallization process are hollow and long needles, and their bulk density and bombing performance are greatly limited due to the high energy density at the tip, large porosity, and poor fluidity. Surprisingly, the particle size and morphology of NGu can effectively be improved by the recrystallization process. In this article, the recrystallization process by directly adding cold water to control temperature is first proposed, aiming to improve the morphological characteristics and reduce the particle size of NGu. Through single factor experimental research, the influences of various operating parameters on the morphology and particle size of NGu during recrystallization process were studied in detail. The results showed that the smallest average particle size of NGu was 19.8 μm when the crude NGu concentration, cold water temperature, volume ratio of boiling to cold water, stirring speed, and polyvinyl alcohol concentration were 5 g/100 mL, 0°C, 1:1, 800 rpm, and 0.35 g/100 mL, respectively. Correspondingly, the morphology of NGu was short rod, which was helpful to improve the bulk density. This novel recrystallization process has great potential to improve the NGu morphological characteristics, providing a new idea for the preparation of military NGu with small particle size and high bulk density.